The Representation of Politeness in EFL Clasroom: An Investigation of Language Used by Lectures and Students in STKIP PGRI Bangkalan - Maimuna Maimuna; Chairuddin Chairuddin; Siti Maria Ulfa (Universitas PGRI Madiun, 2021)
Politeness is a person's politeness in speaking, so that between the speaker and the listener do not feel threatened (offended) in politeness, there are two opinions namely the politeness strategy and the politeness principle. Both are the same, only differ in classifying. Politeness strategy consists of off record, on record, negative politeness and positive politeness. The politeness principle, consist of the tact maxim, generosity maxim, approbation maxim, modesty maxim, sympathty maxim and agreement maxim. This study examined conversations between lecturers and students. The samples of this research were from screenshot of the teaching-learning conversation between lecturers and students via whatsapp. Collecting the data, analyzing and classifying were conducted word by word. The results of this study were students and lecturers often used language clearly and to the point, which is included on the record, namely using the sentence directly and also they used politeness priciple